2020
DOI: 10.3389/fmolb.2020.00109
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in Blood Malignancies

Abstract: Circular (circ)RNAs influence a wide range of biological processes at least in part by interacting with proteins and microRNAs. CircRNAs expressed in the hematopoietic compartment have been increasingly recognized as modulators of physiological and pathological features of hematopoetic stem cell (HSC)-derived populations. In particular, several circRNAs were found to enhance or suppress tumor progression in blood malignancies such as leukemias and lymphomas. Moreover, numerous circRNAs have been proposed to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 78 publications
0
30
0
Order By: Relevance
“…circRNAs generally work by titrating miRNAs binding to mRNAs, thus influencing transcript stability and translation with implications in cancer [ 97 ]. circRNAs are aberrantly expressed in different tumor types and have been associated with both tumor initiation and progression in solid and hematologic malignancies [ 98 , 99 , 100 ]. In laryngeal squamous cell carcinoma, abnormal expression of circRNAs strongly correlates with malignant behavior.…”
Section: Novel Regulators Of the Igf System And Their Impact In Camentioning
confidence: 99%
“…circRNAs generally work by titrating miRNAs binding to mRNAs, thus influencing transcript stability and translation with implications in cancer [ 97 ]. circRNAs are aberrantly expressed in different tumor types and have been associated with both tumor initiation and progression in solid and hematologic malignancies [ 98 , 99 , 100 ]. In laryngeal squamous cell carcinoma, abnormal expression of circRNAs strongly correlates with malignant behavior.…”
Section: Novel Regulators Of the Igf System And Their Impact In Camentioning
confidence: 99%
“…In other studies, performed by Huang et al, the circRNA circAF4 was identified as having an oncogenic role in MLL- rearranged leukemias [ 147 ]. More on the role of circRNAs in hematopoiesis and in hematological malignancies can be found [reviewed in [ 148 , 149 , 150 ].…”
Section: Other Classes Of Non-coding Rnas and Their Role In Progenmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a class of non-coding RNAs with closed ends covalently originating from splicing processes known as back-splicing [ 59 ]. Their circular structure makes them much more stable than normal ncRNAs and highly conserved between species [ 60 ].…”
Section: Circrnasmentioning
confidence: 99%
“…CircRNAs affect various cellular processes through the induction of mRNA transcription or through acting as sponges (ceRNAs) for some miRNAs [ 61 ]. Although their role in the hematopoietic compartment is increasingly being recognized, circRNAs’ expression and function related to CLL remain largely unclear [ 59 ]. Interestingly, the majority of circRNAs produced by plasma cells come from Immunoglobulin (Ig) genes [ 62 ], creating speculation on their possible differential functions in CLL related to IGHV H mutational status.…”
Section: Circrnasmentioning
confidence: 99%